Correction: Heo et al. (2024). How Are Perfectionism Groups Determined Among Korean College Students? Applying the Best-Fitting Short Form of Hewitt and Flett’s Multidimensional Perfectionism Scale (HF-MPS) to a Korean Sample. Psychology International, 6(4), 1028–1039 - Jungyeong Heo; Yaacov Petscher; Insu Paek (Psychology International)
In the original publication [...]